2020
DOI: 10.1021/acs.orglett.0c01317
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic C–C Cleavage/Alkyne–Carbonyl Metathesis Sequence of Cyclobutanones

Abstract: A ring-opening/alkyne–carbonyl metathesis sequence of alkyne-tethered cyclobutanones catalyzed by AgSbF6 is realized for the first time to furnish multisubstituted naphthyl ketones under mild conditions. A range of substrates decorated with various substituents at different positions were all well accommodated. Preliminary mechanistic studies show that silver salt acted as a Lewis acid to facilitate both C–C cleavage of the cyclobutanone moiety and the subsequent metathesis between CO and CC bonds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 94 publications
1
18
0
Order By: Relevance
“…The reaction was sluggish using Cu(OTf) 2 (entry 5), and no reaction occurred in the presence of Zn(OTf) 2 or ZnCl 2 (entries 6 and 7). In accordance with the recognition that the residual water might participate in the reaction, [9] addition of H 2 O into the mixture improved reaction yield, and the highest yield was achieved when the reaction was carried out with 4.5 equivalent of H 2 O (entries 8 and 9). The studies on the solvent effect showed that trichloromethane was still the best medium (entries 10-12).…”
supporting
confidence: 61%
See 3 more Smart Citations
“…The reaction was sluggish using Cu(OTf) 2 (entry 5), and no reaction occurred in the presence of Zn(OTf) 2 or ZnCl 2 (entries 6 and 7). In accordance with the recognition that the residual water might participate in the reaction, [9] addition of H 2 O into the mixture improved reaction yield, and the highest yield was achieved when the reaction was carried out with 4.5 equivalent of H 2 O (entries 8 and 9). The studies on the solvent effect showed that trichloromethane was still the best medium (entries 10-12).…”
supporting
confidence: 61%
“…[8] We recently developed a Ag-catalyzed ring-opening metathesis sequence of alkynetethered cyclobutanones (Scheme 1b). [9] Inspired by this result, we envisioned that Lewis acid would promote direct ringopening reaction of β-phenylcyclobutanones towards 4-phenyl enone compounds. As the continuation of our research on ringopening reaction of small ring compounds, [10] herein we disclosed a ring-opening reaction of simple cyclobutanones catalyzed by low-cost iron catalysts, leading to α, β-unsaturated ketones, a ubiquitous key structure in bioactive molecules and organic building blocks (Scheme 1).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Ideally, several issues should be addressed: (a) independent catalytic cycles should be initiated by simple adjustment of the reaction factor(s) to enable high yield and stereoselectivity; 8-10 (b) nonprecious metals and ligands without toxic additives would be more favorable; [14][15][16][17][18] (c) water is the rst choice of the hydrogen donor for TH process; 10,[19][20][21][22] (d) alkynes with various substituents should be hydrogenated in high yield and stereoselectivity in mild conditions, and over-reduction to saturated alkanes need to be avoided. 23,24 Based on our interest in Ni-catalyzed reaction and alkyne transformations, [25][26][27] We launched a project with nickel catalysts to address the above challenges. After laborious trials, we realized an unprecedented Ni-catalyzed stereodivergent TH of alkynes with water in a novel controlling mode, in which the key to the success of modulation is the judicious inclusion of the base.…”
Section: Introductionmentioning
confidence: 99%